Efektivitas Pelaksanaan Peraturan Daerah Kabupaten Lembata Nomor 9 Tahun 2015 Tentang Perlindungan dan Pengelolaan Kawasan Mangrove Berbasis Masyarakat : (Studi di Desa Merdeka Kecamatan Lebatukan Kabupaten Lembata) - Markus Arianto Kia Wuwur; Saryono Yohanes; Hernimus Ratu Udju (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to analyze the effectiveness of the implementation of Lembata Regency Regional Regulation Number 9 of 2015 concerning the protection and management of community-based mangrove areas (study in Merdeka Village, Lebatukan District, Lembata Regency). This research is empirical legal research, namely directly observing the research location to find out the facts that occur in the field. The research data sources are primary data and secondary data which are then analyzed descriptively qualitatively. The results showed that the implementation of Lembata Regency Regional Regulation Number 9 of 2015 concerning Protection and Management of Community-Based Mangrove Areas has not run effectively and efficiently, due to the lack of serious attention from the government to the protection and management of mangrove areas. The inhibiting factor in the implementation of Regional Regulation Number 9 of 2015 concerning Protection and Management of Community-Based Mangrove Areas is the lack of socialization carried out by the government and the lack of government roles and responsibilities in protecting and managing mangrove areas.